Importance and motives of preferential trade agreements in the EU’s external trade - Kawecka-Wyrzykowska, Elżbieta (Economics and Business Review, 2020)
As a result of previous multilateral negotiations tariff rates are generally lowand cannot explain the reasons for recent proliferation of preferential trade agreements(PTAs). The aim of the paper is to look for other motivations of EU PTAs and to assesstheir importance for the EU. The main research methods are statistical, review and assessmentof WTO documents and critical analysis of literature.First, the present level of tariff protection on selected import markets was estimated.This level illustrates the scale of countries’ interest in their elimination of the existingtariffs. Also the share of preferential imports in the EU extra-trade was calculatedand compared with trade on MFN basis. Next, reasons for PTAs were identified. Theconclusions prove that 21st century PTAs are mainly motivated not by a reduction oftariffs but by the willingness to reduce the regulatory barriers (contained in rules onpublic procurement, environmental protection, etc.). The most dynamic trade nowadaysinvolves flows of accessories and services. In this situation the importance ofPTAs results from the fact that they serve as instruments eliminating national regulatorybarriers faced by exporters of goods and resources on foreign markets. ThusPTAs support production and sales abroad. In the EU political motivations of PTAsare important as well.